The Role Of The Head Of The Religious Affairs Office (Kua) In Minimizing Unrecorded Marriages (Case Study In Kua Pematang Jaya District) - Haniyah Haniyah; Fatimah Zahara; Imam Yazid (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study aims to find out the reality of unrecorded marriages in Pematang Jaya District. To find out how the role of the Head of KUA Pematang Jaya in minimizing marriage is not recorded in the community in Pematang Jaya. To find out what obstacles faced by KUA Pematang Jaya District in minimizing marriage are not recorded in the community in Pematang Jaya. The type of research used is descriptive research, while the data analysis used is qualitative descriptive data analysis. The author obtained this data source through direct interviews with the parties, namely the Head of KUA Pemtatang Jaya. In this study, what is included in the secondary data is literature research. The role of the Religious Affairs Office (KUA) of Pematang Jaya District in minimizing marriage under hand, including Coordinating work with all sectors (village heads, hamlet heads) that support the implementation of the effectiveness of marriage registration in various ways including giving reprimands, to amils / clerics who have intentionally or unintentionally married men and women, the Office of Religious Affairs collaborates with ustadz and religious leaders to convey counseling and guidance to the community of all villages in Pematang Jaya District on how important a marriage is recorded from every religious kegatan both recitations and others, Conducting counseling on Marriage Registration and Happy Family conducted by the Marriage Advisory, Guidance and Preservation Agency (BP4) at the Office of Religious Affairs to prospective brides and guardians. There are several things that become obstacles faced by KUA, including the very limited economic income of the community in their daily lives. So they reasoned that they were unable to pay the administrative costs in KUA as well as transportation costs to travel the distance to KUA. There is still a lack of awareness and understanding of the law in the community among people in Pematang Jaya sub-district who do not realize and fully understand how important marriage registration is. The low level of education studied by the community in Pematang Jaya sub-district, where the perpetrators of marriage are under their hands.